Prayer as Embodied Approach to Deification in Romans 8:1–17: An Interdisciplinary Approach Highlighting the Roles of the Holy Spirit and the Human Spirit - Feng, Jacob Chengwei (Journal of spiritual formation & soul care, 2025)
The doctrine of deification has been experiencing a renaissance of interest in the Protestant West. However, it is not an exaggeration to say that, by and large, deification has been probed as an intellectual exercise. If deification is indeed indispensable to Christian theology, then what does that entail for every Christian in her daily spiritual life in general and prayer in particular? As an interdisciplinary study, this proposal aims to explore the function of prayer in deification by engaging in Cognitive Science, Pauline soteriology, and Watchman Nee’s spirituality. The proposal argues that prayer serves as an embodied approach to deification and highlights the roles of the Holy Spirit and the human spirit. The paper is significant in that, based on the theological reflections of Wright and Nee, the interweaving of prayer, deification, and embodiment helps overcome some long-held Platonic, disembodied Christian concept of “going up to heaven” and the dualism between “flesh” and “spirit.”